Flexibility supply chain in Industrialised Building System (IBS) - Kassim, Umar; Abdullah, S.; Mohamed Udin, Zulkifli (2013)
It is irrefutable that the construction industry is in need of a highly technological construction method or system for the simple aim of giving it a push it deserves.In Malaysia this technologically enhanced method is known as the industrialised Building System (IBS).Concerted efforts have been made for the past decade by various responsible parties especially by the government. Therefore, the IBS 'Road Map' 2003-2010 was introduced and now continues with the IBS 'road map' 2011-2015.However, its performance is still at its infancy, which target is only at an initial stage This study seeks to identify and analyse the factor of the IBS' system's supply chain flexibility as a factor on the success of the system itself.It has been a suspicion that there exists a condition and situation where the supply chain is too rigid and is not flexible in fulfilling the needs and demands of the IBS development in Malaysia.This inflexible situation has brought about a broad range of problems and has stood in the way of the development of the industrialised building system, despite it being introduced since 1964. or 49 years ago. Flexibility in the IBS supply chain is very important and is associated with other industries like transportation, manufacturing industry, and others.Up until now, we have yet to disco~er any special studies related to the flexibility in the IBS supply chain in this country.Responding to this challenge, this research is hoped to be able to probide sufficient feedback to the solution to the IBS supply chain flexibility issue.The researcher is confident that the poor system flow of supply chain has impeded the advancement of the Industrialised Building System that has long been open to debate.